AUTHORITY OF THE ELECTION SUPERVISORY BODY REGARDING CAMPAIGN PRODUCTS (Based on Bawaslu Regulation number 20 of 2018 concerning prevention of violations and disputes general election process) - Andri, Alvi (Inspiring Law Journal, 2024)
In every election held in Indonesia, even though it is held once every five years, it has legal instruments in the form of statutory regulations as regulations, and the rules of the game in the election are known to each contestant participating in the Pemuli, but there are still types and forms. violations committed by them and the winning success team who supported the election participant candidates. One of the types and forms of election violations in question is the use and placement of campaign props (APK) which are media tools for introducing candidates with their vision and mission and the programs they offer if they are elected and occupy their positions as legislative representatives of the people and/or heads of regions or even as President and Vice President. To overcome this, it is hoped that Bawaslu together with the KPU and Regional Government and related legal apparatus will be able to overcome and take action against all matters related to election violations, especially the use and placement of Campaign Display Equipment (APK) itself. This type of research uses a normative juridical approach and uses qualitative analysis techniques which are then explained and analyzed using descriptive analytical methods. The type of approach used in writing this thesis is a library research approach, namely by studying books and documents related to the topic of the article and also using a statutory regulatory approach, namely by reviewing existing statutory regulations. related to the topic discussed in this research. The results of the research and discussion in this study showed that the frequent types and forms of violations in the implementation of the use and placement of Campaign Props (APK) caused by Election participants were not due to a lack of socialization by Bawaslu and the KPU regarding the rules for the use and placement of Campaign Props (APK). . However, it is more about the arrogance possessed by each participant who took part in the election contestation. The impact of APKs installed haphazardly is not only on the aesthetic value for the environment, but can also have implications for the imposition of administrative and criminal election sanctions, which can lead to the disqualification of election participants themselves